2018
DOI: 10.1186/s12957-018-1347-0
|View full text |Cite
|
Sign up to set email alerts
|

Need for normalization: the non-standard reference standard for microvascular invasion diagnosis in hepatocellular carcinoma

Abstract: BackgroundPreoperative microvascular invasion (MVI) assessment in hepatocellular carcinoma (HCC) is one of the current research focuses, with studies reporting controversial results regarding MVI-associated risk factors. As a possible source of bias, reported MVI rate (percentage of MVI-positive patients) varies a lot among studies. Pathological examination should have been the golden criteria of MVI diagnosis, but no standard and generally adopted pathological examination protocol exists.Methods and resultsIt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The ancillary findings including bile duct invasion, perineural invasion, and tumor grade were also recorded. Pathological samples were collected using a 7‐point baseline sample collection protocol . However, for IMCC that manifested as a solitary tumor with a maximum diameter of ≤3 cm, the whole tumor should be sampled .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ancillary findings including bile duct invasion, perineural invasion, and tumor grade were also recorded. Pathological samples were collected using a 7‐point baseline sample collection protocol . However, for IMCC that manifested as a solitary tumor with a maximum diameter of ≤3 cm, the whole tumor should be sampled .…”
Section: Methodsmentioning
confidence: 99%
“…Pathological samples were collected using a 7‐point baseline sample collection protocol . However, for IMCC that manifested as a solitary tumor with a maximum diameter of ≤3 cm, the whole tumor should be sampled . MVI was defined as a tumor within a vascular space lined by endothelium that was visible only at microscopy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, many studies have indicated adjuvant transarterial chemotherapy after hepatic resection could help to improve long-term survival in MVIpositive patients (4)(5)(6)(7)(8). However, previous studies showed the MVI positive rate after hepatectomy in pathology report varied substantially, from 7.8 to 57.1% (9). Thus, an accurate and standardized report of MVI is needed for precise patient stratification and consequent individualized treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, HCC sampling focuses on confirmation of the histological features of HCC, completeness of surgical excision, and cirrhosis condition ( 20 , 21 ). Given that MVI is unevenly distributed in the adjacent liver parenchyma around HCC ( 2 ), traditional sampling method usually resulted in false-negative detection ( 9 ). The MVI rate under traditional sampling was reported varied from 7.8 to 28.4% ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%